Consumer Attitudes Toward Foreign versus Local Brands in Emerging Markets A Study Based on the Consumer Goods Industry in Brazil - Stoebe, Martin Johannes (Hamburger Schriften zur Marketingforschung, 2013)
Emerging markets are more important than ever for consumer goods companies from the developed world that face stagnating markets and intense competition at home. While in the past companies were successful by targeting the premium end of these markets, the biggest growth opportunities are now among the large and booming middle class. Yet, increasingly sophisticated local competitors are equally targeting this segment. The author investigates this phenomenon in the emerging market of Brazil. This research is the first to focus on the attitudes of Brazilian consumers toward perceived brand foreign- versus localness. Starting from an extensive overview of existing literature, the author draws on theories from the fields of new institutional economics, neo behaviorism and consumer culture to construct a sophisticated research model. Empirical research confirms that increasing foreignness leads to greater brand prestige, while higher levels of localness result in greater brand sincerity and a closer self-brand connection. By demonstrating how local brand appeal influences key affective drivers of consumer decision making, this research contributes significantly to the scientific marketing literature. It is also highly relevant for business practitioners. Both foreign and domestic brands can benefit from higher levels of perceived localness. Companies need to reflect this in their brand positioning and support it, for example by using local testimonials, sponsoring local events or even acquiring local brands